The ผลการใช้คอนเทนต์รีวิวอาหารร่วมกับกิจกรรมการสื่อสารโดยใช้เกมเป็นฐานเพื่อส่งเสริมการขายของผู้ประกอบการรายย่อยในมหาวิทยาลัยผ่านการเรียนรู้ด้วยการบริการสังคม: The Results of Using Food Review Content together with Game-Based Communication Activities to Promote the Sales of Small Entrepreneurs in Universities through Social Service Leaning - ธรรมวิภัชน์, กุลธิดา (วารสารวิจัยและนวัตกรรม สถาบันการอาชีวศึกษากรุงเทพมหานคร, 2023)
งานวิจัยครั้งนี้มีวัตถุประสงค์เพื่อ1) ออกแบบและผลิตคอนเทนต์รีวิวอาหารร่วมกับกิจกรรมการสื่อสารโดยใช้เกมเป็นฐานเพื่อส่งเสริมการขายของผู้ประกอบการรายย่อยในมหาวิทยาลัย 2) เพื่อประเมินผลการรับรู้และความพึงพอใจของผู้ชมที่มีต่อสื่อและกิจกรรมที่พัฒนาขึ้น และ3) เพื่อศึกษาผลประเมินตนเองของนักศึกษาผ่านการเรียนรู้ด้วยการบริการสังคม เครื่องมือที่ใช้ประกอบด้วย 1) คอนเทนต์รีวิวอาหารบนโซเชียลมีเดียร่วมกับกิจกรรมการสื่อสารโดยใช้เกมเป็นฐาน 2) แบบประเมินคุณภาพ 3) แบบประเมินผลการรับรู้ 4) แบบประเมินความพึงพอใจของกลุ่มตัวอย่าง 5) แบบประเมินตนเองผ่านการเรียนรู้ด้วยการบริการสังคมในรายวิชา ETM358 Marketing Communication ภาคการศึกษาที่ 2/2565 โดยเก็บรวบรวมข้อมูลจากกลุ่มตัวอย่างโดยวิธีเลือกแบบเจาะจงจากผู้ประกอบการรายย่อยที่เข้าร่วมโครงการเป็นเวลาไม่ต่ำกว่า 1 เดือน และเป็นผู้ชมที่ยินดีตอบแบบสอบถาม จำนวน 30 คน สถิติที่ใช้ได้แก่ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน และ t-test ผลการวิจัยพบว่า ผลการออกแบบและพัฒนาสื่อโปสเตอร์และเขียนคอนเทนต์รีวิวอาหารและเครื่องดื่มจำนวน 30 ชิ้นจาก 30 ร้านค้า วิดีโอคอนเทนต์ 7 ชิ้น และกิจกรรมการสื่อสารโดยใช้เกมเป็นฐาน จำนวน 1 กิจกรรม แล้วจึงนำไปให้ผู้เชี่ยวชาญจำนวนด้านละ 3 ท่านประเมินคุณภาพ พบว่า 1) ผลการประเมินคุณภาพด้านเนื้อหาและด้านสื่อการนำเสนออยู่ในระดับดีมาก 2) ผลประเมินด้านการรับรู้ของผู้ชมอยู่ในระดับมากที่สุด ผลประเมินความพึงพอใจของผู้ชมอยู่ในระดับมาก และ3) ผลประเมินตนเองผ่านการเรียนรู้ด้วยการบริการสังคมมีผลประเมินหลังเรียนสูงกว่าก่อนการเรียนอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 คำสำคัญ : คอนเทนต์รีวิวอาหาร กิจกรรมการสื่อสารโดยใช้เกมเป็นฐาน ผู้ประกอบการรายย่อย การเรียนรู้ด้วยการบริการสังคม Abstract The aims of this research were 1) to create and develop food review content together with a game-based communication activity to promote the sales of small entrepreneurs in the university; 2) to evaluate the audiences' perception and satisfaction to the media and activity developed; and; 3) to assess students' self-evaluation through social service learning. The tools employed in this research included: 1) food review content posted on social media, accompanied by a game-based communication activity, 2) quality assessment form, 3) Perception assessment form, 4) Satisfaction assessment form, and, 5) self-assessment form for social service learning as part of the ETM358 Marketing Communication course in the second semester of 2022. The data were collected through purposive sampling, selecting small entrepreneurs who had been involved in the project for a minimum of 1 month and were willing to respond to the questionnaire as the audiences. The statistical methods employed included mean, standard deviation, and t-test. The findings of the research were as follows: the design and development phase resulted in 30 food and beverage review posters, content from 30 different shops, 7 video contents, and 1 game-based communication activity. These materials were subsequently reviewed by 3 experts in each aspect to assess their quality. The results were as follow: 1) the evaluation indicated a very good level of quality in both the content and presentation media, as well as the activity itself, 2) he assessment of audiences perception revealed the highest level of positive response. Moreover, the satisfaction assessment demonstrated a high level of satisfaction among the small entrepreneurs, 3) the self-assessment conducted through social service learning exhibited a significant increase in learning evaluation after the program, with statistical significance at the .05 level.